The Relation of Metaphysics to Political Theory in the Thoughts of Al-Farabi - Hadi, Amirul (Buletin Al-Turas, 2024)
PurposeThis article explored the extent to which metaphysics has a fundamental relation with politics in the thoughts of Al-Farabi.MethodIn this study, the descriptive-analysis method was adopted, as it attempted to describe Al-Farabi’s thoughts on metaphysics and its relation to his political theory. This was then to be followed by philosophical and historical approaches to the subject.Result/findingAl-Farabi’s substantive thoughts fell into two major divisions: metaphysics and politics. Politics properly was intended to achieve the ultimate aim of human beings, which was happiness (al-sa‘adah) or perfection (al-kamal). The highest perfection that man desires to attain is intellectual perfection (al-kamal al-nazari). A city (state), which he calls “al-Madinah”, became a whole similar to the cosmos, and its members—based on their classes—were to cooperate toward achieving happiness. It was through this way that a perfect city/state (al-madinah al-fadilah) would be realized.ConclusionPolitical theory of Al-Farabi encompassed both psychological and cosmological elements. Yet, it was strongly connected to metaphysics. This could be observed in the notion that political science was aimed at the prosperity of men as members of the political community. Al- Farabi’s thoughts began with metaphysics or cosmology and moved towards psychology and physiology, and ended with the discourse on politics.